EPIZOOTOLOGICAL PECULIARITIES OF THE COURSE OF CATTLE AND SHEEP PARASITOSES IN THE SUMMER PASTURE PERIOD - Yevstafieva, V.; Kruchynenko, O.; Melnychuk, V.; Mykhailiutenko, S.; Korchan, L.; Shcherbakova, N.; Dolhin, O. (Scientific Progress & Innovations, 2020)
Parasitic diseases of ruminants are widely spread in many countries and cause significant economic losses to livestock farming. Intensification of this branch affects the species composition, prevalence and intensity indices of the invasion, as well as the peculiarities of the course of parasitoses. The study of separate aspects of the epizootological process in animal parasitic disease will allow to prevent their occurrence and to implement effective preventive measures in time. The research was conducted at the Laboratory of the Department of Parasitology and Veterinary- Sanitary Expert Examination of Poltava State Agrarian Academy. The aim of the study was to elucidate the peculiarities of spreading cattle and sheep parasitoses during the summer pasture period. According to the results of coproovoscopic studies, it has been found that cattle are affected by pathogens of trichuriasis, fasciolosis and eimeriosis, in which the average prevalence of parasitoses infestation is 75.0 %. The intensity of helminthic invasions, on average, ranged from 8.28 to 12.50 eggs in 1 g of feces, and eimeriosic – was 29.13 oocysts/g. In 83.33 % of cases, mono-invasions were diagnosed (eimeriosic – 60 %, trichurosic – 20 % and fasciolosic – 20 %). Eimeriosis-trichurosis (16.66 % of the total number of diseased animals) was registered in mixed invasions. It has been found that sheep in the summer-pasture period are affected by strongilates of the digestive organs, trichurises, strongyloides and eimeries, and prevalence of infection was 20.0 %. The intensity of helminthic invasions, on average, ranged from 28.0 to 232.0 eggs/g, and eimeriosic – was 652 oocysts/g. Sheep parasitoses in sheep were mostly in the form of poly-invasions (71.43 % of the total number of diseased animals), which were represented by two- (90.48 % of detected poly-invasions) and three-component (9.52 %) associations of helminthes and coccidia. Simultaneous course of strongyloidiasis and strongylatosis of digestive organs was most often detected (76 % of detected poly-invasions). Mono-invasions were diagnosed in 28.57 % of infected animals. They were represented by two varieties: strongyloidiasis (63.64 % of the number of animals suffering from monoinvasion), and strongylatosis (36.36 %).